Influence of Independent Director, Female Director, and Thin Capitalization on Tax Avoidance - Sintong Josua Parlindungan Simamora; Dian Purnama Sari (JAFFA, 2021)
This study aims to examine the effect of independent directors, female directors, thin capitalization on tax avoidance. This research design is quantitative with hypothesis. The object of this research is non-financial sector companies listed on the Indonesia Stock Exchange for the 2017-2019 period. The data analysis technique is multiple linear regression. Independent directors by looking at the proportion of the number of independent directors from the total members of the board, with the results of independent directors giving negative results on tax avoidance. Female directors also looked at the number of female directors from the total board members, with the result that female directors had a positive influence on tax avoidance. Thin capitalization as measured by Maximum Amount Debt (MAD), with the result of thin capitalization has no effect on tax avoidance. Tax avoidance is measured using the Book-tax Gap (BTG).  This research is useful for companies in making decisions related to the structure of directors and the company's capital structure and especially the government to evaluate the performance of state revenues.